Return to sport and patient satisfaction in athletic populations following meniscal allograft transplantation: a narrative review - Derrick M. Knapik; Aghogho Evuarherhe, Jr; Joshua T. Kaiser; Kyle R. Wagner; Reem Darwish; Nolan B. Condron; Brian J. Cole (Journal of Cartilage & Joint Preservation, 2022)
Introduction: Meniscal injuries represent the most common pathology affecting the knee, often limiting return to sporting activities secondary to pain and disability. In meniscal deficient patients, meniscal allograft transplantation (MAT) procedure may be considered. Return to sport (RTS) rate, predictors of successful RTS, and patient-reported outcomes in athletic patients undergoing MAT are largely unknown. Objectives: To review the literature on RTS rates, predictors of RTS success or failure, and patient-reported outcomes following MAT in athletic patients. Methods: PubMed, Cochrane, and Scopus databases were reviewed for relevant literature using the following keywords: “meniscal allograft transplantation,” “meniscal transplant,” “meniscus transplant,” “return to sport,” “return to play,” and “patient-reported outcomes.” Results: RTS rates following MAT are generally favorable in the athletic population. Appropriate graft sizing, secure graft fixation, younger age, and the absence of articular cartilage injury are associated with improved RTS success. Meanwhile, the presence of focal chondral defects, osteoarthritic changes, limb malalignment, concomitant procedures performed at the time of MAT, and ligamentous instability are associated with failed RTS. Significant improvements in patient-reported outcomes were appreciated when compared to pre-operative values. Conclusions: MAT is a viable treatment option for athletic, meniscal deficient patients. Future investigations of high methodologic quality that evaluate long-term outcomes, graft survivorship, and athletic performance following MAT are warranted to better understand the influence and efficacy of MAT in athletic patients.